What's in a brand name? Preferences of mobile wallets in India under a shifting regulation. (18th September 2020) - Reyes-Mercado, Pavel; Karthik, M.; Mishra, Ram Kumar
This paper analyses adopters' preferences on mobile wallets and model individual decisions in a financial environment under shifting regulations on know your customer and recent demonetisation. We used conjoint analysis to identify the utility contributions of wallets' attributes and levels. Findings from 275 questionnaires from urban sample in India show that the most important attribute is the brand name with 59%, followed by cash back amount, and fee per transfer/payment. For brand name, incumbent brands exhibited a positive utility to adopters while emerging brands presented a negative utility. For cash back amount, wallet adopters only favoured the highest level of 30% and they signalled with negative utilities the remaining two lower options. For fees, the sample found positive utility in the lowest fee of 3%. Noteworthy, the least important variable was the number of friends as proxy to assess the impact of network effects.